Does the local food environment around schools affect diet? Longitudinal associations in adolescents attending secondary schools in East London - Smith, Dianna (BioMed Central, 2013)
BACKGROUND: The local retail food environment around schools may act as a potential risk factor for adolescent diet. However, international research utilising cross-sectional designs to investigate associations between retail food outlet proximity to schools and diet provides equivocal support for an effect. In this study we employ longitudinal perspectives in order to answer the following two questions. First, how has the local retail food environment around secondary schools changed over time and second, is this change associated with change in diet of students at these schools? METHODS: The locations of retail food outlets and schools in 2001 and 2005 were geo-coded in three London boroughs. Network analysis in a Geographic Information System (GIS) ascertained the number, minimum and median distances to food outlets within 400 m and 800 m of the school location. Outcome measures were ‘healthy’ and ‘unhealthy’ diet scores derived from adolescent self-reported data in the Research with East London Adolescents: Community Health Survey (RELACHS). Adjusted associations between distance from school to food retail outlets, counts of outlets near schools and diet scores were assessed using longitudinal (2001–2005 n=757) approaches. RESULTS: Between 2001 and 2005 the number of takeaways and grocers/convenience stores within 400 m of schools increased, with many more grocers reported within 800 m of schools in 2005 (p< 0.001). Longitudinal analyses showed a decrease of the mean healthy (−1.12, se 0.12) and unhealthy (−0.48, se 0.16) diet scores. There were significant positive relationships between the distances travelled to grocers and healthy diet scores though effects were very small (0.003, 95%CI 0.001 – 0.006). Significant negative relationships between proximity to takeaways and unhealthy diet scores also resulted in small parameter estimates. CONCLUSIONS: The results provide some evidence that the local food environment around secondary schools may influence adolescent diet, though effects were small. Further research on adolescents’ food purchasing habits with larger samples in varied geographic regions is required to identify robust relationships between proximity and diet, as small numbers, because of confounding, may dilute effect food environment effects. Data on individual foods purchased in all shop formats may clarify the frequent, overly simple classification of grocers as ‘healthy’.